Necesidad de reformar el artículo 119 de la ley orgánica del servicio público, relacionadas con las enfermedades profesionales. - Quizhpe Salinas, Ángel Serafín (2011)
Occupational diseasesdespite beinga constantin the workforceof public servantsand deservespriority treatment inthelegal and medicalaspects- legal, however, arecovered bythe Labor Codewith aworker'sapproachin general and notparticularizedpublic servantin theirrespectivelistand compensation, and, worse still the currentpublicService LawArticle 119in theconfusionwhen consideringevidenceof occupational accidentsandoccupational diseasesmotivated bywhat isinappropriateconceptual, doctrinaland legally. The dynamicsof the labor activityof public servants, work environment and use oftechnology determinethe appearanceof new diseaseswhich requires theregular updatingof the listof occupational diseasesthusconstituterightsof public servantsand debtthe Statethroughits institutionsand companies shouldprovideadequate conditionsfor work. Work accidentsand occupational diseasesdifferfromthe views ofconceptual, legal and doctrinal, in that order aregenerallylinked toworkerandpublic servants. Demonstrated inresearchthat occupational diseasesare derived fromthe work activityof public servants andtherefore it isnecessarytoreformitavailable to thePublic ServiceAct, an action islegallyjustified.